Safe longitudinal platoons of vehicles without communication - Scheuer, A.; Simonin, O.; Charpillet, F. (2009 IEEE International Conference on Robotics and Automation, 2009)
This paper deals with the platooning problem that can be defined as the automatic following of a manned driven vehicle by a convoy of automatic ones. Different approaches have been proposed so far. Some require the localisation of each vehicle and a communication infrastructure, others called near-to-near approach only needs vehicle on-board sensors. However, to our knowledge, they do not provide any proof of non collision. We propose a novel near-to-near longitudinal platooning building a collision-free platooning whatever the number of vehicles. The model is derived from the study of the most dangerous interaction between two vehicles, i.e. considering the maximum acceptable acceleration when the previous vehicles brakes at maximum capacity. Collision avoidance of this model is proved. Finally, we show that this model can be combined to existing ones, keeping this collision-free property while allowing more various behaviors.